Properties of the line-of-sight velocity field in the hot and X-ray-emitting circumgalactic medium of nearby simulated disk galaxies - ZuHone, John A.; Schellenberger, Gerrit; Ogorzałek, Anna; Oppenheimer, Benjamin D.; Stern, Jonathan; Bogdán, Ákos; Truong, Nhut; Markevitch, Maxim; Pillepich, Annalisa; Nelson, Dylan; Burchett, Joseph N.; Khabibullin, Ildar; et al. (The astrophysical journal, 2024)
The hot, X-ray-emitting phase of the circumgalactic medium of massive galaxies is believed to be the reservoir of baryons from which gas flows onto the central galaxy and into which feedback from active galactic nuclei and stars inject mass, momentum, energy, and metals. These effects shape the velocity fields of the hot gas, which can be observed via the Doppler shifting and broadening of emission lines by X-ray integral field units. In this work, we analyze the gas kinematics of the hot circumgalactic medium of Milky Way-mass disk galaxies from the TNG50 simulation with synthetic observations to determine how future instruments can probe this velocity structure. We find that the hot phase is often characterized by outflows from the disk driven by feedback processes, radial inflows near the galactic plane, and rotation, although in some systems the velocity field is more disorganized and turbulent. With a spectral resolution of ∼1 eV, fast and hot outflows (∼200-500 km s−1) can be measured, depending on the orientation of the galaxy on the sky. The rotation velocity of the hot phase (∼100-200 km s−1) can be measured using line shifts in edge-on galaxies, and is slower than that of colder gas phases but similar to stellar rotation velocities. By contrast, the slow inflows (∼50-100 km s−1) are difficult to measure in projection with these other components, but may be detected in multicomponent spectral fits. We find that the velocity measured is sensitive to which emission lines are used. Measuring these flows will constrain theories of how the gas in these galaxies evolves.
Gesehen am 29.11.2024